Hesitations and reconfigurations in the management of visitor flows in outstanding natural areas - Vincent Vles (Via@)
For natural areas considered as outstanding, issues related to the governance and the ways of managing visitor flows, as well as the improvement of the quality and the experience of the visit, are expressed in terms of sustainable mobility, access to data concerning the visit, collaborative consumption, participation and dialogue between local inhabitants, shopkeepers, visitors and site managers. This paper reports the main results of research evaluating the way in which seven outstanding natural sites in France approach this question. It draws from the experiments conducted a series of lessons and questions that were debated in January 2017 at the French National Assembly with members of the Grands Sites de France Network. It contributes to knowledge of the user experience, and how the latter is taken into account by the regions responsible for the management of these areas. The growing importance of immaterial factors in regulating flows of visits to these areas combined with the radical paradigm shift that now considers natural common resources as being both material and immaterial help, by their development, to determine the tourism regulation of these exceptional sites. The analysis of perceptions and representations contributes to the knowledge of the methods of optimizing nature and establishes concerted intervention with visitors as a major factor in local development.